Strategi Mediasi dalam Menekan Kasus Perceraian Dini di Pengadilan Agama Medan - Maharani, Riski; Lubis, Fauziah (Kamaya: Jurnal Ilmu Agama, 2025)
Having a mediator in this case is very important, apart from making peace, a mediator is also responsible for helping both parties to make peace and reach an agreement on what both parties want. A mediator’s ability to mediate is really needed, especially in certain cases, to be a mediator you must have expertise or be competent. However, the mediation process is not always successful in helping the dispute resolution process. In reality, the divorce rate in Indonesia is increasing, as is what is happening in the Medan Religious Courts. This research aims to examine the strategies applied by mediators in resolving early divorce cases at the Medan Religious Courts, as well as to assess the level of success of mediators in mediating early divorce cases based on data for 2023. This research uses a qualitative approach with a focus on the quality of the objects studied and applies descriptive methods to related subjects. The approach used is juridical-sociological, by observing social phenomena from a legal perspective. Data sources were obtained through literature study and interviews with mediators at the Medan Religious Court. The results of the research show that mediator at the Medan Religious Court applies seven main strategies in mediating early divorce cases: the mediator must know the situation of the case very well, find out what the desires of both parties are, come up with a solution that is acceptable to both parties, and apply a religious, psychological, beautiful past and family approach. It can be said that the effectiveness achieved by mediators in resolving early divorce cases at the Medan Religious Court has not been effective and efficient. However, several factors that influence the success of mediation, both internal and external, have also been identified. Internal factors can come from the litigants.